The Role of Notaries in the Drafting of Prenuptial Agreements: An Islamic Family Law Perspective - Ajeng Rahma Pratiwi; Fadhil Aliffin; M. Ridlo Alan Naufal; Ayu Nurpiah (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
Marriage constitutes an institution with religious, social, and legal dimensions, both within the framework of Islamic law and the positive law of Indonesia. In line with the increasing complexities of marital life, particularly in economic matters and property ownership, the need for prenuptial agreements as instruments of legal protection has become increasingly relevant. Prenuptial agreements serve to regulate the rights and obligations of the parties and to minimize potential conflicts in the future. In practice, the role of the notary is highly significant, as notaries are authorized to draw up authentic deeds that possess perfect evidentiary value and provide legal certainty. Nevertheless, a gap persists between the practice of drafting prenuptial agreement deeds and the principles of Islamic family law, both in terms of substance and implementation. Furthermore, limited public understanding, as well as the insufficient expertise of some notaries in Islamic family law, constitute additional challenges in the application of such agreements. This study aims to analyze the role of notaries in the drafting of prenuptial agreement deeds and to assess their conformity with the perspective of Islamic family law. The research employs a qualitative method with a normative juridical approach complemented by a sociological approach. Data are obtained through literature review, documentation, and interviews as supporting data. The findings of this study are expected to contribute theoretically to the development of Islamic family law and to serve as a practical reference for notaries and the public in formulating prenuptial agreements that align with principles of justice and prevailing legal provisions.